The acquisition of French : the development of inflectional morphology and syntax in L1 acquisition, bilingualism, and L2 acquisition - Prévost, Philippe, 1966- (Language acquisition & language disorders, 2009)
This book presents a thorough description of morphosyntactic knowledge developed by learners of French in four different learning situations - first language (L1) acquisition, second (L2) language acquisition, bilingualism, and acquisition by children with Specific Language Impairment - within the theoretical framework of generative grammar. This approach allows for multiple comparisons across acquisition contexts, which provides the reader with invaluable insights into the nature of the acquisition process. The book is divided into four parts each dealing with a major morphosyntactic domain o.